PRACTICAL RECOMMENDATIONS FOR OVERCOMING ETHNOCULTURAL BARRIERS IN COMMUNICATION BETWEEN REPRESENTATIVES OF RUSSIAN AND CHINESE ETHNOS - P. Yakupov; N. Chizhikova (Вестник университета)
The main practical recommendations intended to overcome the ethnocultural barriers that arise between representatives of the Russian and Chinese ethnos in the process of communication are presented. The recommendations are based on the results of the dissertation research, which identified the main ethno -cultural barriers in business communication between representatives of the Russian and Chinese ethnos, as well as the statements of the group of experts on the issue of intercultural business communication. At the end of the article, a conclusion is made about the use of the derived recommendations.